Liquid Emulsion Membrane Stabitiy Studies for Removal of Nickel from Liquid Aqueous Waste - Hasan, M.A.; Atwa, S.T.; El-Taweel, A.A. (Asian Journal of Chemistry, 2015)
Stability of the liquid emulsion membrane (LEM) is a measure of its leakage during the operation of metals extraction in liquid emulsion membrane process. As liquid emulsion membrane stability decreases, the permeation of metal ions decreases due to release of the internal stripping aqueous phase containing the extracted metals to the external aqueous phase, which reverses some of the metal already extracted. Liquid- liquid extraction of nickel ions from acetate media was first investigated using di-2-ethylhexylphosphoric acid as an extractant diluted with cyclohexane as a diluent. The results showed that the optimum conditions for extraction of nickel ions from acetate media were as follows, pH 8 at the feed solution containing 0.01 M ammonium acetate, 6 % di-2-ethylhexylphosphoric acid as a carrier, 0.1 M sulfuric acid as a stripper and cyclohexane as a diluent. The different parameters affecting the stability of the prepared liquid emulsion membrane were studied; pH values at the feed solution; surfactant types and concentrations; emulsification time and speed; volume ratios of emulsion to feed solution; and ammonium acetate concentration in the feed solution. The result obtained well be used to prepare a stable membrane to study the permeation and removal of nickel from aqueous waste solution.